Zervikales und linksthorakales Weichteilemphysem bei einer 49-jährigen beatmeten Patientin = Subcutaneous cervical and left thoracic emphysema in a 49-year-old woman on ventilation - El-Battrawy, Ibrahim; Frambach, Daniel; Behnes, Michael; Münz, Benedikt; Lehmann, Ralf; Borggrefe, Martin; Akın, Ibrahim (Der Internist, 2015)
We report the case of a 49-year-old woman who was admitted with community-acquired pneumonia. The medical state worsened despite administration of antibiotics. She was intubated and ventilated because of respiratory distress. Several hours after intubation, she developed massive subcutaneous emphysema. The bronchoscopy showed tracheal transmural rupture 3 cm long on the posterior wall of the trachea. The high-risk surgery and massive doses of catecholamine favoured conservative treatment with bilateral endobronchial intubation and veno-venous extracorporeal membrane oxygenation. The patient made a full recovery.